IPASS: A Study on the Tolerability and Effectiveness of Injectable Testosterone Undecanoate for the Treatment of Male Hypogonadism in a Worldwide Sample of 1, 438 Men. (19th July 2012) - Zitzmann, Michael; Mattern, Andreas; Hanisch, Jens; Gooren, Louis; Jones, Hugh; Maggi, Mario
ABSTRACT Introduction. Morbidity/mortality is higher in men with below‐normal serum testosterone. Restoring testosterone to normal is beneficial. Aim. Assessment of safety and effectiveness of injectable long‐acting testosterone undecanoate (TU) in hypogonadal men in daily clinical practice. Methods. An international, multicenter, one‐arm, prospective observational study in 23 countries. Main Outcome Measures. Parameters of erectile function, libido, vigor/vitality, mood, and ability to concentrate assessed by physician interview using items and five‐point Likert scales. Physical and circulatory parameters as well as hematocrit, prostate‐specific antigen (PSA) levels, glucose control, and lipid profiles. IPASS. An International, multicenter, Post‐Authorisation (after authorized use in respective country) Surveillance Study on long‐acting‐intramuscular TU conducted at 155 centers in 23 countries in Europe, Asia, Latin America, and Australia. Patients received up to five TU injections during 9–12 months. Results. Of the 1, 493 hypogonadal men enrolled, 1, 438 (aged 49.2 ± 13.9 years) having received 6, 333 injections were analyzed. Scores of mental and psychosexual functions (libido, vigor, overall mood, and ability to concentrate) improved markedly, while mean waist circumference decreased from 100 to 96 cm. Blood pressure and lipid parameters were altered in a favorable and significant manner. After four TU injection intervals, the percentage of patients with "low" or "very low" levels of sexual desire/libido decreased from 64% at baseline to 10%; moderate, severe, or extremely severe erectile dysfunction decreased from 67% to 19%. At the last observation, 89% of patients were "satisfied" or "very satisfied" with TU therapy. Adverse events and adverse drug reactions (ADRs) occurred in 12% and 6% of patients, respectively, mostly mild to moderate. The most common ADRs were increase in hematocrit, increase in PSA, and injection site pain (all <1%). No case of prostate cancer was observed. Conclusion. In this largest worldwide sample of hypogonadal men, injectable long‐acting TU was effective and well tolerated. Zitzmann M, Mattern A, Hanisch J, Gooren L, Jones H, and Maggi M. IPASS: A study on the tolerability and effectiveness of injectable testosterone undecanoate for the treatment of male hypogonadism in a worldwide sample of 1, 438 men. J Sex Med **;**:**–**.